An Overview of Sentiment Analysis: Concept, Techniques, and Challenges - Nalawat, Mudita (Indian Journal of Computer Science, 2019)
"Data is the new oil," a statement given by UK based mathematician, Clive Humby very accurately suits the current scenario of the World Wide Web. The unimaginable usage of online opinion sharing platforms is resulting in the generation of a large volume of opinion-rich data. This opinion rich data can be in the form of reviews given by people regarding any product, brand, service or something related to their experience and emotion about any topic. This data can be used by organizations to know what their customers really think, want, and need. Sentiment analysis is one of the technologies working behind this analysis. It is the process of mining text to extract subject information which can help organizations understand the social sentiments behind their product or service. This paper focuses on the aspects related to sentiment analysis. Various techniques that can be applied to sentiment analysis are discussed in this paper. This paper also focuses on how sentiment polarity of the data can be obtained using various sentiment classification techniques. Various applications and challenges related to sentiment analysis will also be explained in this paper.